Transformer Load Calculator & Simulator for 70kV Seduduk Putih Substation: Statistical Analysis and Prediction - Nur Aldillah Julita; Syamsir Abduh; Farid Wijaya (Jurnal Teknik Elektro Indonesia, 2026)
This study aimed to analyze the load patterns of two power transformers at the 70kV Seduduk Putih Substation using descriptive statistical approaches, load analysis, and Multiple Linear Regression based on hourly data throughout 2024. The analysis focused on two main transformers with a capacity of 30 MVA each, employing descriptive statistics and regression methods to identify distribution, trends, and relationships between variables. The results indicate that the average load of the two transformers at the 70kV Seduduk Putih Substation is as follows: Transformer 1 operates at 60% of its maximum load, while Transformer 2 operates at 45% of its maximum load. This suggests that the average loads of both transformers remain below 80%, which is considered normal/safe. However, the peak load analysis shows that Transformer 1 reaches a maximum load of 92.08%, and Transformer 2 reaches 87.03%, indicating that their peak loads exceed 80%. Load data was collected periodically for specific periods, including hourly, monthly, and peak load measurements. Multiple Linear Regression was used to evaluate the relationship between time and transformer load. The findings reveal that the transformers exhibit distinct load patterns for each month, with a moderate correlation to time as indicated by the R-Square value. The peak load analysis identifies critical times with potential overloading risks. This study is expected to serve as a reference for PLN, the operator of the substation, in making operational decisions.